Reabilitação de Edifícios - Do diagnóstico à conclusão da obra - Vasco Peixoto de Freitas (2003)
Buildings rehabilitation requires a new approach methodology and an indispensable understanding of the process by the various intervening parties. This information sheet includes the proposal of a methodology for drawing up rehabilitation projects, with the definition of the various stages of the process, as well as the elements that are to make them up. A case study is also presented regarding to the rehabilitation of a building located in Porto, with the aim of analysing the difficulties experienced during the retrofitting process.KEYWORDS: Rehabilitation, diagnosis, rehabilitation techniques